Reconstruction of Extensive Diaphragmatic Defects Using the Rectus Abdominis Muscle and Fascial Flap - Shumpei Kato; Hisashi Sakuma; Takako Fujii; Ichiro Tanaka; Junichi Matsui (Archives of Plastic Surgery, 2023)
Diaphragmatic reconstruction is required for extensive diaphragmatic defects associated with tumor resection. Methods using artificial mesh and autologous tissues, such as pedicled flaps, have been reported predominantly for diaphragmatic reconstruction. We present the case of a 61-year-old woman who presented with a 14 × 13 × 12 cm tumor in the abdominal cavity of the upper left abdomen on computed tomography. The diaphragm defect measuring 12 × 7 cm that occurred during excision of the malignant tumor was reconstructed using the rectus abdominis muscle and fascial flap. The flap has vertical and horizontal vascular axes; therefore, blood flow is stable. It also has the advantage of increasing the range of motion and reducing twisting of the vascular pedicles. Fascial flap does not require processing such as thinning and can be used during suture fixation. This procedure, which has rarely been reported so far, has many advantages and may be a useful option for diaphragm reconstruction.